Data mining and safety analysis of voriconazole in patients with a hematological malignant tumor based on the FAERS database: differences between children and adults - Li, Hao; Jiang, Manxue; Pan, Xiaona; Kong, Lingti (Frontiers in Pharmacology, 2025)
ObjectiveVoriconazole is a broad-spectrum antifungal agent. It is used widely for the prevention and treatment of invasive fungal infections in patients with a hematological malignancy, but studies on its safety in this population are scarce. We assessed the adverse drug events (ADEs) of voriconazole in this population based on the US Food and Drug Administration Adverse Event Reporting System (FAERS) database to improve understanding of the safety of voriconazole.Research design and methodsADE reports for patients with a hematological malignant tumor using voriconazole between the first quarter of 2004 to the first quarter of 2024 were retrieved. Then, they were classified using the preferred terminology (PT) and system organ category (SOC) in the Medical Dictionary for Regulatory Activities. Data mining was done using reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and multi-item gamma Poisson shrinker (MGPS).ResultsA total of 605 ADEs were included: 116 (19.17%) in children and 489 (80.83%) in adults. The types of SOC involved in children and adults were 22 and 24, respectively. The only positive SOC signal that satisfied all four algorithms simultaneously in children was “psychiatric disorders”, whereas in adults they were “endocrine disorders” and “hepatobiliary disorders”. At the PT level, the types involved in children and adults were 28 and 74, respectively. The highest ROR signal intensities were found for “hallucinations, mixed” in children and “toxic optic neuropathy” in adults. The median time of onset of the ADE in children and adults was 11 and 8.5 days, respectively.ConclusionWe used four algorithms (ROR, PRR, BCPNN, MGPS) to mine the signals of voriconazole in patients with a hematological malignant tumor, and compared the differences between children and adults. This study is important for targeting the monitoring, and could help to improve the safety of voriconazole.